Compressive crushing of granite with wear-resistant materials. - Heino, Vuokko; Kaipiainen, Mikko; Siitonen, Pekka; Ratia, Vilma; Valtonen, Kati; Lepistö, Toivo; Kuokkala, Veli-Tapani (2011)
Uniaxial crusher is a non-standard wear testing device designed and used at the Tampere Wear Center for evaluating the wear resistance of materials in compressive crushing. In this study, various wear resistant materials were tested and their wear surfaces characterized with scanning electron microscopy. In addition, the general suitability of the device for wear testing was evaluated. Abrasive wear was the most common wear mechanism observed on the studied surfaces. Moreover, marks of surface fatigue were also seen. The material loss was mostly due to plastic deformation. Higher hardness was found to correlate with improved wear resistance, especially in cases where wear was purely abrasive.
jufo:1